DNA methylation in spermatozoa as a prospective marker in andrology. (22nd August 2013) - Kläver, R.; Tüttelmann, F.; Bleiziffer, A.; Haaf, T.; Kliesch, S.; Gromoll, J.
Summary: Recent studies have shown associations of aberrant DNA methylation in spermatozoa with idiopathic infertility. The analysis of DNA methylation of specific genes could therefore serve as a valuable diagnostic marker in clinical andrology. For this purpose, rapid and reliable detection methods, reference values and the temporal stability of spermatozoal DNA methylation need to be established and demonstrated. In this prospective study, swim‐up purified semen samples from 212 consecutive patients (single samples), 31 normozoospermic volunteers (single samples) and 10 normozoospermic volunteers (four samples at days 1, 3, 42 and 45 plus a fifth sample after 180–951 days) were collected. Spermatozoal DNA was isolated, bisulphite converted and DNA methylation was analysed by pyrosequencing. DNA methylation of the maternally imprinted gene MEST was measured in samples of 212 patients and 31 normozoospermic volunteers and the temporal stability of eight different genes and two repetitive elements was examined in consecutive samples of 10 normozoospermic volunteers. MEST DNA methylation was significantly associated with oligozoospermia, decreased bi‐testicular volume and increased FSH levels. A reference range for spermatozoal MEST DNA methylation (0–15%) was established using the 95th percentile of DNA methylation in normozoospermic volunteers. Using this reference range, around 23% of our patient cohort displayed an aberrant MEST DNA methylation. This epigenetic aberration was found to be significantly associated with bi‐testicular volume, sperm concentration and total sperm count. DNA methylation in normozoospermic volunteers was stable over a time period of up to 951 days in contrast to classical semen parameters. Our data show that MEST DNA methylation fulfils the prerequisites to be used as routine parameter and support its use during andrological workup if a prognostic value can be shown in future.